Understanding inequality within households - Ingvild Almås; Charlotte Ringdal; Ingrid Hoem Sjursen (Global Labor Organization (GLO), 2021)
To describe and understand the economic inequality in a given so- ciety, it is necessary to understand intra-household inequality. House- holds can hide important inequalities, but can also be essential units for redistribution in society. This paper gives an overview of within- household distributions in different settings, both between the adults and also between adults and children. It documents that there are sub- stantial inequalities within households in some contexts and that these often, but not always, disfavor women and children. The paper also discusses the importance of intra-household allocations for poverty and inequality measurement. Methods that assign each household member a per-adult share of household consumption leads to underestimation of inequalities and miss-classification of poverty. In comparison, struc- tural models seem to do better in predicting individual poverty when disaggregated data on allocation within households are not available. Main determinants of power in household decision-making are also discussed, and relatedly, so are two important policy questions: Are targeted transfers to women good for female empowerment? And, are targeted transfers to mothers good for child outcomes? The empirical evidence is clearly pointing to targeting being beneficial for female empowerment, but the evidence is less clear when it comes to child outcomes.
Keywords: D13; D63; J13; 330; Within-household resource allocation; inequality; measurement